Gender inequality in the Nordic film industry: Exploring above-the-line positions in film production - Loist Skadi; Ehrich Martha Emilie; Radziwill Sophie; Prommer Elizabeth (Nordic Journal of Media Studies)
In this article, we explore the enduring barriers to gender equality in the Nordic film industry, with a focus on positions of power and structural biases. Despite considerable efforts over the past decades to highlight gender inequality – resulting in more women in creative positions in Sweden, Denmark, and Finland – a significant gap remains. Our analysis of 1,070 films produced and released theatrically between 2010 and 2020 in Denmark, Finland, Iceland, Norway, and Sweden shows men dominating directing, writing, and producing roles in 75 per cent of the cases, with women slightly more present in producing. The study finds a negative correlation between the dominance of men in producing roles and the presence of women in directing and writing roles. Factors such as the size of the creative team and co-production had less impact on the proportion of women in key creative positions than expected, whereas a higher proportion of women in managerial roles is linked to an increased presence of women in positions of directing (Sweden) and writing (Finland). These results indicate that while some progress has been made, structural barriers still significantly hinder gender equality in the industry.